300 Gastric Submucosal Lipomatosis Presenting as Gastric Polyposis: The First Case Report and Morphometric Study of Additional 127 Gastric Bypass Specimens With a Proposal for Diagnostic Criteria. (11th January 2018) - Chumbalkar, Vaibhav; Fu, Zhiyan; Boguniewicz, Ann; Lee, Hwajeong
Abstract: Introduction: Gastric lipomatosis (GL) is an extremely rare entity where gastric submucosa is diffusely expanded by accumulation of fat, but without well-defined histological criteria. GL presenting as multiple polyps is not reported in the literature. We encountered such a case in a bariatric partial gastrectomy specimen, which prompted the current study to assess extent of fat in gastric submucosa in morbidly obese patients. Methods: H&E slides of 128 bariatric partial gastrectomy specimens including the index case were examined. The amount of submucosal fat was categorized as 0 (no fat), 1 (up to 70% fat), and 2 (> 70% fat). The maximum submucosal thickness was measured with the interval cutoff of 5 mm (radiologic upper normal thickness) and 10 mm. Results: The index case was of a 46-year-old morbidly obese man, who underwent preoperative endoscopy followed by bariatric partial gastrectomy. Multiple gastric polyps were noted endoscopically as well as grossly upon pathologic examination. Histological evaluation revealed GL with polypoid thickening of the submucosa up to 12 mm by fat. Of the 128 cases, seven (5.4%) fell in category 0, 90 (70.3%) in category 1, and 31 (24.2%) in category 3. Maximum submucosal thickness was <5 mm in 104 (81.3%) and ≥5 mm in 24 (18.8%) cases, in which three (2.3%) cases, including the index case, showed ≥10 mm of submucosal fat. Conclusions: We report a first case of GL presenting as gastric polyposis. Gastric submucosa is significantly thickened by fat and/or shows diffuse fat accumulation in 18.8% and 24.2% of morbidly obese patients, respectively. Based on our findings, we propose a submucosal thickness of a minimum of 10 mm and diffuse (>70%) fat accumulation as diagnostic criteria for GL. Using these criteria, the prevalence of GL in the morbidly obese population is 2.3%. A subset of these may present as polyps and gastric polyps secondary to GL may be under-recognized.